2023
DOI: 10.3389/fpsyg.2022.974382
|View full text |Cite
|
Sign up to set email alerts
|

The strategies of exercise intervention for adolescent depression: A meta-analysis of randomized controlled trials

Abstract: PurposeThis study aimed to investigate the effect of exercise intervention, and analyze exercise intervention strategies for adolescent depression through a meta-analysis of RCTs.MethodsAccordance to PRISMA guidelines, PubMed, Medline, EBSCO, Web of Science, SPORTDiscus, PsycINFO, ProQuest, and CNKI were searched for eligible records. Peer-reviewed studies were included if they met the following criteria: population (mean age of 10–18 years), intervention (physical activity, sport, or exercise), and outcomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Physical exercise has a positive impact on the prevention and treatment of depression ( 10 ). An exercise intervention study of 433 adolescents with depression showed that moderate- to high-intensity exercise had a significant therapeutic effect on adolescent depression and was significantly better than low-intensity exercise, in addition to the moderate and sustained positive effects of the exercise intervention on adolescent depression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise has a positive impact on the prevention and treatment of depression ( 10 ). An exercise intervention study of 433 adolescents with depression showed that moderate- to high-intensity exercise had a significant therapeutic effect on adolescent depression and was significantly better than low-intensity exercise, in addition to the moderate and sustained positive effects of the exercise intervention on adolescent depression ( 11 ).…”
Section: Introductionmentioning
confidence: 99%